Intrapartum Cardiotocography Status (Reactive or Non Reactive) in Pregnant Women Presenting with Meconium-stained Liquor and their Perinatal Outcome - Neelofur Shehzad, Urooj Naz, Aruna Kumari Hira, Aneela Habib, Saira Bhatti, Naveeta Jitesh, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the prevalence of reactive intrapartum cardiotocography status in pregnant women presenting with meconium-stained liquor (MSL) and their perinatal outcome. Study design: Descriptive Cross-sectional study Study setting: This study was conducted in the department of Obstetrics & Gynaecology, Civil Hospital, Karachi. Duration of study: September 10, 2022 to March 9, 2023. Subject and Methods: All those patients fulfilling the inclusion and exclusion criteria were included in the study after taking informed consent and demographic data was obtained. The status of the amniotic membranes, if ruptured whether artificially or spontaneously, colour and amount of liquor was observed clinically and was also recorded. CTG was performed in every patient for 30 minutes in the left lateral position on admission as well as a monitoring tool in labour at an interval of more than 4 hours. The CTG was classified as reactive or non-reactive. By visual examination meconium stained liquor was classified as grade 1, 2 and 3 after spontaneous rupture of membrane or artificial rupture of membranes. The fetal outcome in terms of APGAR score at 1 minute and 7 minute and NICU admission was recorded. SPSS - 27 was used for data analysis. Results: 114 (76%) delivered vaginally and 36 (24%) underwent for C-section. 61 (40.7%) of the cases had MSL grade-1, 51 (34.3%) had MSL grade-II and 38 (25%) had MSL grade-III. Reactive Intrapartum Cardiotocography was found in 133 (89%) Pregnant Women presenting with Meconium Stained Liquor (MSL). Out of them, 40 (80%) neonates with reactive cardiotocography were admitted in NICU. Statistically significant difference was observed in the APGAR score at 1 minute and at 7 minute among the reactive and non- reactive neonates. Conclusion: Increasing grades of meconium stained liquor were associated with cardiotocography abnormalities. Increasing grades of meconium stained liquor and cardiotocography abnormalities were associated with increased operative interference. Keywords: Amniotic fluid, CTG, Intrapartum, perinatal outcome